Multistability in a Periodically Forced Brusselator - Rech P.C.* (2021)
© 2020, Sociedade Brasileira de Física.In this paper, we report on multistability in a periodically forced Brusselator, which is modeled by a nonlinear nonautonomous system of two first-order ordinary differential equations. Multistability regions are detected in a cross section of the four-dimensional parameter space of the model, namely the (ω, F) parameter plane, where ω and F are respectively angular frequency and amplitude of an external forcing. Lyapunov exponents spectra are used to characterize the dynamical behavior of each point in the abovementioned parameter plane. Moreover, basins of attraction, bifurcation diagrams, and phase-space portraits are used to illustrate the coexistence of periodic and chaotic behaviors.